2021
DOI: 10.7196/ajtccm.2021.v27i4.158
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the Quick Sepsis-related Organ Failure Assessment (qSOFA) score among critically ill medical and surgical patients with suspected infection in a resourcelimited setting

Abstract: Background. The Quick Sequential Organ Failure Assessment (qSOFA) score is a simple bedside tool validated outside of the intensive care unit (ICU) to identify patients with suspected infection who are at risk for poor outcomes. Objectives. To assess qSOFA at the time of ICU referral as a mortality prognosticator in adult medical v. surgical patients with suspected infection admitted to an ICU in a resource-limited regional hospital in South Africa (SA). Methods. We conducted a retrospective cohort study on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…They concluded that this score is very useful in resource-limited intensive care settings in predicting mortality among critically ill medical or surgical patients having sepsis. 17 We had similar results, and a score of greater than two was associated with increased mortality in our study participants.…”
Section: Discussionsupporting
confidence: 80%
“…They concluded that this score is very useful in resource-limited intensive care settings in predicting mortality among critically ill medical or surgical patients having sepsis. 17 We had similar results, and a score of greater than two was associated with increased mortality in our study participants.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, the prognostic value of the qSOFA scale was very noteworthy in our results, detecting a higher mortality in patients who, at the time of PSC activation, exhibited the three positive factors of the scale. Its ease of implementation makes it a useful tool in an era of limited resources [51]. Very interesting studies have been published regarding the use of automatic alerts for the detection of sepsis, and the use of artificial intelligence, big data, and machine learning in this context, which, although in the preliminary phases for clinical use, are tools that should be kept in mind for use in the near future [52].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the AJTCCM, Bishop et al [18] retrospectively evaluated the role of a positive qSOFA score in predicting mortality in medical and surgical patients with suspected infection from the database of a regional hospital's critical care unit comprising of high care (HC) and ICU patients. The predictive ability of qSOFA for all patients in their database, including those without infections, has been previously reported.…”
mentioning
confidence: 99%
“…The predictive ability of qSOFA for all patients in their database, including those without infections, has been previously reported. [18,19] This cohort of 1 162 patients consists predominantly of surgical patients (60%) who were mechanically ventilated. This is a useful study, and the authors ought to be congratulated for their efforts, considering the paucity of qSOFA data in ICU settings, the need for data from poorly resourced regions and the global lack of qSOFA data for surgical cohorts in particular.…”
mentioning
confidence: 99%